2017
DOI: 10.3389/fphys.2017.00238
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Pathophysiology of Myocardial Fibrosis and Its Quantitative Assessment in Heart Failure

Abstract: Myocardial fibrosis is an important part of cardiac remodeling that leads to heart failure and death. Myocardial fibrosis results from increased myofibroblast activity and excessive extracellular matrix deposition. Various cells and molecules are involved in this process, providing targets for potential drug therapies. Currently, the main detection methods of myocardial fibrosis rely on serum markers, cardiac magnetic resonance imaging, and endomyocardial biopsy. This review summarizes our current knowledge re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 99 publications
(127 reference statements)
3
126
0
2
Order By: Relevance
“…In this work, we covered the fibrosis, which is the apparition of non-conductive (fibrous) tissue patches among the normal myocardium tissue. These patches act as obstacles in the normal myocardium electrical conduction and favor the risk of suffering different kinds of arrhythmias [4], even those ones that cause sudden cardiac death. On the other hand, recent research [5][6][7] sugged that the presence of fragmentation, which is a ECG feature manifesting as a number of extra peaks and deflections in QRS complex, is related to the presence of myocardial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we covered the fibrosis, which is the apparition of non-conductive (fibrous) tissue patches among the normal myocardium tissue. These patches act as obstacles in the normal myocardium electrical conduction and favor the risk of suffering different kinds of arrhythmias [4], even those ones that cause sudden cardiac death. On the other hand, recent research [5][6][7] sugged that the presence of fragmentation, which is a ECG feature manifesting as a number of extra peaks and deflections in QRS complex, is related to the presence of myocardial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…For years myocardial remodeling was regarded as a direct result of myocardial fibrosis . In contrast T2* was regarded as a potential marker of myocardial iron load since it is seldom affected by myocardial fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…For years myocardial remodeling was regarded as a direct result of myocardial fibrosis. 12 In contrast T2* was regarded as a potential marker of myocardial iron load since it is seldom affected by myocardial fibrosis. 13 This research has shown a close relationship of left ventric- SPI is used to evaluate LV geometry and higher SPI value indicates more globular shape of LV.…”
Section: Discussionmentioning
confidence: 99%
“…[7,14,15] recently, myocardial fibrosis is detected by serum markers, cardiac magnetic resonance imaging (CMR) with late gadolinium enhancement (LGE), and endomyocardial biopsy.Though histology of endomyocardial biopsy is regarded as the gold standard, LGE is an established tool to assess the extent of myocardial fibrosis. [16] The main potential mechanism of MF among long long-distance athletes especially marathoners remains to be unknown since not all marathoners develop MF even after a lifelong participation. [6], [17]- [19] Schoor et al hypothesize four different pathways which may cause the development of MF among athletes [7].…”
Section: Mf In Marathonersmentioning
confidence: 99%